Enhancing Collaboration : Joint Management Action Plan. (Policy Papers; Policy Paper ;, 2007)
In March 2006, the Managing Director of the International Monetary Fund (IMF) and the President of the World Bank commissioned the External Review Committee on IMF-World Bank Collaboration to look at the status of institutional collaboration and provide suggestions for improvement. The Committee's report, released in February 2007, called for the strengthening of the culture of collaboration in the two institutions, and made a number of specific proposals in that direction. The Joint Management Action Plan (JMAP) was prepared against this background, and the actions agreed between Bank and Fund managements in the JMAP are scheduled to be presented in informal Board meetings in early October. The JMAP will be launched immediately after the Annual Meetings. The goal is for most new systems to be operational in time for the preparation of FY09 budgets.